The role of communist party into implementation of deportation in Estonia - Saueauk, Meelis (Genocidas ir rezistencija, 2008)
Of all the post-war deportations, the most damaging to Estonia was the Operation Priboj, which was carried out in March 1949 in Lithuania, Latvia and Estonia under the leadership of the Ministry of State Security (MGB). More than 20,000 people were deported from Estonia alone during this operation. By that time, the Soviet leadership had already developed a ‘deportation policy’ based on 30 years of deportation practice and flawless methodology. Decisions on deportations, including even the smallest-scale operations, were taken at the highest levels of the USSR leadership from the mid-1930s at the latest, and close cooperation between the party and repressive structures is evident in deportations.
Keywords: Estonia; Communist party; deportations; repressive structures